Letteratura parascolastica e nazionalismo nella Prima Repubblica - Simões Júnior, Alvaro Santos [UNESP] (My University, 2013)
In the early decades of Brazilian Republic, didactic literature played an important role in contributing to the «spirit of national integration», as José Veríssimo recommended. But, in addition to fighting the «parochialism» of different regions of the vast country, didactic literary works intended to combat the «foreign threat» represented by uncontrolled immigration and the economic and military imperialism. Brief analysis of Contos Pátrios (1894) and A Pátria Brasileira (1909), written by Olavo Bilac and Coelho Neto, and Porque Me Ufano do Meu País (1901), by earl of Afonso Celso, aims to reveal some of the resources used by the authors to elicit the feeling of brotherhood, solidarity and collective bond among Brazilian children, driving away threats that hung over the country. It also indicates that the interpretation of the national past, from which came the heroes, martyrs and leaders to be worshiped and imitated by children, radically opposed the monarchist Afonso Celso and the republicans Bilac and Coelho Neto.

Nei primi decenni repubblicani la letteratura parascolastica ha svolto, come raccomandava José Veríssimo, l’importante funzione di contribuire all’«integrazione dello spirito nazionale». Ma oltre a combattere il «campanilismo» delle diverse regioni del paese, i libri scolastici si proponevano di fronteggiare il «pericolo straniero» rappresentato dall’immigrazione incontrollata e dall’imperialismo economico e militare. Una breve analisi dei Contos pátrios (1894) e A Pátria brasileira (1909), scritti a quattro mani da Olavo Bilac e Coelho Neto, e di Porque me ufano do meu país (1901), del conte de Afonso Celso, rivela alcuni strumenti utilizzati dagli autori per suscitare il sentimento di fratellanza, di solidarietà e di vincolo collettivo fra i bambini brasiliani, scongiurando le minacce che sovrastavano il paese. Si evidenzia anche come l’interpretazione del passato nazionale, dal quale provenivano eroi, martiri e leader che dovevano essere venerati e imitati dai bambini, contrapponesse radicalmente il monarchico Afonso Celso e i repubblicani Bilac e Coelho Neto.
Keywords: Olavo Bilac; Coelho Neto; Conte di Afonso Celso; A Pátria Brasileira; Porque Me Ufano do Meu País; Earl of Afonso Celso